Variability within individuals of plasma ionic magnesium concentrations - Newhouse, Ian J (BioMed Central, 2002)
BACKGROUND: With the invention of the ion-selective electrode (ISE), ionic magnesium (iMg) is a common blood assay. This could be advantageous, as iMg is the biologically active form of Mg. There is some evidence that iMg has considerable within subject variability. RESULTS: Individual ranges averaged .08 mmol/L (range .05 to .14). Coefficients of variation (CV) ranged from 3% to 7% (mean 4%) while analytical variation was determined to be 2.3%. Biological variability thus accounts for almost half of the variability, which is clinically significant, as 9 of the 13 subjects recorded at least one value below a reference range of .46 – .60 mmol/L. A significant within-day variation (p < .001) was noted, with differences between 7:00 and 10:00 as well as 10:00 and 22:00. Between day variations were not significant (p = .56). CONCLUSIONS: A plausible explanation of this data is that iMg has a circadian rhythm. Thus, cautious interpretation of single iMg values is warranted until future research determines the nature of iMg variability.